Product Quality, Brand Awareness, and Price in Purchasing Decisions: Pengetahuan Pajak, Insentif Keuangan, dan Pasar Tenaga Kerja terhadap Pilihan Karier - Fiviana, Kiki Bela; Supardi (Indonesian Journal of Law and Economics Review, 2025)
General Background: Purchasing decisions in UMKM often depend on marketing and product perception. Specific Background: Kedai Sukidayo faces competition that requires understanding how consumers respond to product quality, brand awareness, and pricing. Knowledge Gap: Limited empirical evidence explains how these variables jointly shape consumer decisions in local UMKM contexts. Aims: This study examines the relationships among product quality, brand awareness, price, and purchasing decisions. Results: Using proportional stratified random sampling and regression analysis, the study shows that product quality significantly contributes to purchasing decisions, brand awareness strengthens consumer confidence toward the product, and price plays a supportive role in shaping buyer preference. Novelty: The study integrates these three variables simultaneously within a specific UMKM food business. Implications: Findings highlight the need for UMKM to prioritize consistent product quality, maintain strong brand recognition, and set prices aligned with consumer perceptions. Highlights:• The study identifies key determinants of consumer purchase decisions.• Brand awareness strengthens consumer confidence in local UMKM.• Product quality emerges as the strongest purchasing driver. Keywords: Product Quality, Brand Awareness, Price, Purchasing Decision, UMKM